2022
DOI: 10.3390/cells11152283
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Amino Acid Metabolism Differs between Community-Acquired Pneumonia and Infection-Associated Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Amino acids and their metabolites are key regulators of immune responses, and plasma levels may change profoundly during acute disease states. Using targeted metabolomics, we evaluated concentration changes in plasma amino acids and related metabolites in community-acquired pneumonia (CAP, n = 29; compared against healthy controls, n = 33) from presentation to hospital through convalescence. We further aimed to identify biomarkers for acute CAP vs. the clinically potentially similar infection-triggered COPD ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Creatine and dimethylglycine commonly showed a decrease in blood due to the oxidation of creatine oxidation for AECOPD patients. , 3-Hydroxybutyric acid was increased, which may be attributed to the energy metabolism shift from carbohydrates to lipid utilization and amino acid metabolism in AECOPD . Threonine was found to be a potential biomarker for AECOPD diagnosis. , Fucose may be the degradation product of the fucosylation glycoprotein, which was a biomarker of COPD . These metabolic biomarkers will provide powerful tools for the assessment and management of COPD.…”
Section: Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Creatine and dimethylglycine commonly showed a decrease in blood due to the oxidation of creatine oxidation for AECOPD patients. , 3-Hydroxybutyric acid was increased, which may be attributed to the energy metabolism shift from carbohydrates to lipid utilization and amino acid metabolism in AECOPD . Threonine was found to be a potential biomarker for AECOPD diagnosis. , Fucose may be the degradation product of the fucosylation glycoprotein, which was a biomarker of COPD . These metabolic biomarkers will provide powerful tools for the assessment and management of COPD.…”
Section: Results and Discussionmentioning
confidence: 97%
“…87 Threonine was found to be a potential biomarker for AECOPD diagnosis. 88,89 Fucose may be the degradation product of the fucosylation glycoprotein, which was a biomarker of COPD. 90 These metabolic biomarkers will provide powerful tools for the assessment and management of COPD.…”
Section: Enhanced Metabolic Fingerprints For Copd Diagnosismentioning
confidence: 99%
“… 24 , 25 Metabolomics exploration has already been carried out in the diagnosis, molecular mechanism, syndrome diagnosis and pharmacodynamic mechanism of COPD; however, the associated metabolomics characteristics and clinical application need still to be improved in the future. 26 , 27 At present, some researches based on a targeted or untargeted metabolomics have suggested that dysregulated metabolism including amino acid, lipid and glycerophospholipid may be recognized as biomarker candidates for the acute exacerbation of COPD, 20–23 but the early diagnosis of COPD based on the serum or plasma metabolites or panels is also still insufficient. With the help of metabolomics, relying on a high-throughput and high-sensitivity metabolic analysis platform, the endogenous small molecule metabolites in COPD patients can be qualitatively or quantitatively analyzed, and specific biomarkers can be found.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study based on a targeted metabolomics suggested dysregulated amino acid metabolism in community-acquired pneumonia and some metabolites such as asparagine/threonine may be recognized as biomarker candidates for the infection-triggered COPD exacerbation. 20 Moreover, abnormalities in lipid metabolism may underlie AECOPD as early-diagnostic biomarkers. 21 , 22 In addition, a comparative study reported numerous plasma metabolites may be considered as candidate biomarkers for diagnosis or prognosis of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the clinical application of targeted AA metabolism has attracted increasing interest in medical science. Considering the strong correlation of AA metabolism with inflammation and immunity, several studies have been initiated in the field of chronic lung disease research 8–12 . Some AAs have been used as severity or prognosis markers.…”
Section: Introductionmentioning
confidence: 99%